A review: Solar cell current scenario and future trends - Choubey, P C; Oudhia, A; Dewangan, R (Recent Research in Science and Technology, 2012)
In recent years solar cell technology has achieved tremendous growth as sustainable source of energy. In last few years photovoltaic industries have emerged with an annual growth of 40%.Solar cells are renewable pollution free source of electrical energy which can easily replace traditional fossil fuels. In this article we have reviewed the previous and current status of various generations of solar cells and discussed about their future trends and aspects.